Impacts of urbanization and landscape pattern on habitat quality using OLS and GWR models in Hangzhou, China - Zhu, Congmou; Zhang, Xiaoling; Zhou, Mengmeng; He, Shan; Gan, Muye; Yang, Lixia; Wang, Ke (Ecological indicators, 2020)
•Spatiotemporal pattern of habitat quality in Hangzhou was assessed by InVEST model.•Spatial distribution of habitat quality showed positive spatial auto-correlation.•Negative impact of urbanization on habitat quality varied with time and space.•Impacts of landscape pattern on habitat quality differed in magnitude and direction. China has experienced the most serious habitat degradation, especially in fast-growing metropolis cities. Although increasing attentions have been brought to this issue, we still lack the understanding of the quantitative impacts of urbanization and landscape pattern on habitats. In this study, we used the “Integrated Valuation of Environmental Services and Trade-off” (InVEST) model to evaluate the habitat quality in Hangzhou city. We further employed spatial auto-correlation to analyze its spatiotemporal pattern variation characteristics. Finally, the ordinary least squares (OLS) and geographically weighted regression (GWR) models were used to explore the impacts of urbanization and landscape pattern change on habitat quality. The results show that the habitat quality index of Hangzhou decreased from 0.608 to 0.577 during 2004–2015, and these areas mainly located around the suburb decreased significantly. The spatial distribution of habitat quality showed significantly positive spatial auto-correlation, and the overall spatial auto-correlation degree of the habitat quality increased during this time. Rapid urbanization has significant negative effects on habitat quality in various areas, while the magnitude and direction of the impacts of landscape pattern on habitat quality differed in time and space. These results provide decision-making criteria for formulating differential urban development policies and landscape management measures for urban ecological sustainability.